PRIVATE DENSITY ESTIMATION FOR MIXTURE DISTRIBUTIONS AND GAUSSIAN MIXTURE MODELS - Afzali Kharkouei, Mohammad (My University, 2024)
We develop a general technique for estimating (mixture) distributions under the constraint of differential privacy (DP). On a high level, we show that if a class of distributions (such as Gaussians) is (1) list decodable and (2) admits a “locally small” cover (Bun et al., 2021) with respect to total variation distance, then the class of its mixtures is privately learnable. The proof circumvents a known barrier indicating that, unlike Gaussians, GMMs do not admit a locally small cover (Aden-Ali et al., 2021b). As the main application, we study the problem of privately estimating mixtures of Gaussians. Our main result is that poly(k, d, 1/α, 1/ε, log(1/δ)) samples are sufficient to estimate a mixture of k Gaussians in R^d up to total variation distance ``α'' while satisfying (ε, δ)-DP. This is the first finite sample complexity upper bound for the problem that does not make any structural assumptions on the GMMs.
Keywords: Distribution Learning; Differential Privacy; Gaussian Mixture Models; Density Estimation